Empirical relationship between macroeconomic volatility and stock returns: Evidence from Latin American markets - Abugri, Benjamin A (International Review of Financial Analysis, 2008)
Emerging market stock returns have been characterized as having higher volatility than returns in the more developed markets. But previous studies give little attention to the fundamentals driving the reported levels of volatility. This paper investigates whether dynamics in key macroeconomic indicators like exchange rates, interest rates, industrial production and money supply in four Latin American countries significantly explain market returns. The MSCI world index and the U.S. 3-month T-bill yield are also included to proxy the effects of global variables. Using a six-variable vector autoregressive (VAR) model, the study finds that the global factors are consistently significant in explaining returns in all the markets. The country variables are found to impact the markets at varying significance and magnitudes. These findings may have important implications for decision-making by investors and national policymakers. © 2006 Elsevier Inc. All rights reserved.
66 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-059-421-200-229 tex.type: [object Object]
Keywords: Emerging markets; Latin America; Macroeconomic volatility; Stock returns; Vector autoregressive model; dept.eco; dept.fin